Long‐term stability of peri‐implant tissues after bone or soft tissue augmentation. Effect of zirconia or titanium abutments on peri‐implant soft tissues. Summary and consensus statements. The 4th EAO Consensus Conference 2015. Issue 11 (September 2015) - Sicilia, Alberto; Quirynen, Marc; Fontolliet, Alain; Francisco, Helena; Friedman, Anton; Linkevicius, Tomas; Lutz, Rainer; Meijer, Henny J.; Rompen, Eric; Rotundo, Roberto; Schwarz, Frank; Simion, Massimo; et al.
Abstract: Introduction: Several surgical techniques and prosthetic devices have been developed in the last decades, aiming to improve aesthetic, hygienic and functional outcomes that may affect the peri‐implant tissues, such as procedures of bone and soft tissue augmentation and the use of custom‐made abutments of titanium and zirconium. Materials and methods: Three systematic reviews, based on randomized clinical trials and prospective studies covering the above reported topics were analysed, and the detected evidence was exposed to interactive experts' discussion during the group's and general assembly's meetings of the 4th EAO Consensus Conference. The results are reported using the following abbreviations: S‐T: short‐term evidence, M‐T: medium‐term evidence; L‐T: long‐term evidence; LE: limited evidence. Results: Soft tissue augmentation procedures may be indicated for the increase of soft tissue thickness and keratinized tissue, the reduction of interproximal peri‐implant bone loss, and the coverage of shallow peri‐implant soft tissue recessions (S‐T, LE), L‐T is lacking. Guided bone regeneration approaches (GBR) showed efficacy when used for ridge reconstruction after the complete healing of the soft tissues (S‐T & L‐T), and the stability of the augmented bone may play a role in the maintenance of the soft tissue position and dimensions (LE). No significant differences were observed between titanium and zirconia abutments when evaluating probing pocket depth, bleeding on probing, marginal bone levels and mucosal recessions. Zirconia abutments were associated with more biological complications but demonstrated superiority in terms of achieving natural soft tissue colour (S‐T).